A comparative study of publicly accessible web-based idea portals. (1st January 2011) - Finzen, Jan; Kintz, Maximilien; Kobes, Stefan
This article presents results from a survey of web-based idea portals. We focus on such portals that allow users to publicly utter and discuss new ideas or provide solutions to previously announced problems. We note that the number of such portals has been continuously growing ever since the late nineties and are concerned with the question of how to support interested companies in selecting a suitable portal.